Similarity and granger causality in Polish and Spanish stock market sectors during the COVID-19 pandemic - Dorota Żebrowska-Suchodolska; Iwona Piekunko-Mantiuk (Comparative Economic Research. Central and Eastern Europe, 2022)
Capital markets react almost immediately to crises. Such relationships can be both international and local. The research focuses on the stock markets of two countries: Spain and Poland. These countries are often compared in terms of various economic and social criteria. The research covers the period from March 3, 2019, to March 31, 2021. The aim is to identify sectors and indices similar to each other at the local level and to identify, among pairs of similar indices, those that provide a boost to another sector. The research uses the hierarchical cluster analysis method (Ward's method) and the Granger causality test. This work presents a novel approach to sectoral comparison at the local level.
Keywords: C32; C38; G01; G14; 330; coronavirus; economic sectors; financial volatility; similarity